The endocytic protein intersectin is a major binding partner for the Ras exchange factor mSos1 in rat brain - Tong, Xin-Kang (Oxford University Press, 2000)
We recently identified intersectin, a protein containing two EH and five SH3 domains, as a component of the endocytic machinery. The N–terminal SH3 domain (SH3A), unlike other SH3 domains from intersectin or various endocytic proteins, specifically inhibits intermediate events leading to the formation of clathrin-coated pits. We have now identified a brain-enriched, 170 kDa protein (p170) that interacts specifically with SH3A. Screening of combinatorial peptides reveals the optimal ligand for SH3A as Pp(V/I)PPR, and the 170 kDa mammalian son-of-sevenless (mSos1) protein, a guanine-nucleotide exchange factor for Ras, con– tains two copies of the matching sequence, PPVPPR. Immunodepletion studies confirm that p170 is mSos1. Intersectin and mSos1 are co-enriched in nerve terminals and are co-immunoprecipitated from brain extracts. SH3A competes with the SH3 domains of Grb2 in binding to mSos1, and the intersectin–mSos1 complex can be separated from Grb2 by sucrose gradient centrifugation. Overexpression of the SH3 domains of intersectin blocks epidermal growth factor-mediated Ras activation. These results suggest that intersectin functions in cell signaling in addition to its role in endocytosis and may link these cellular processes.